1164. County-Level Geographic Distribution of Extended-Spectrum Cephalosporin-Resistant Enterobacteriaceae Across Outpatient Settings of the Veterans Health Administration, 2000–2017. (26th November 2018) - Goto, Michihiko; Nair, Rajeshwari; Livorsi, Daniel; Schweizer, Marin; Ohl, Michael; Richardson, Kelly; Beck, Brice; Alexander, Bruce; Perencevich, Eli
Abstract: Background: Extended-spectrum cephalosporin resistance (ESCR) among Enterobacteriaceae has emerged globally over the last two decades, with increased prevalence in the community. Data from European countries and healthcare-associated isolates in the United States have demonstrated substantial geographic variability in the prevalence of ESCR, but community-onset isolates in the United States have been less studied. We aimed to describe geographic distribution and spread of ESCR among outpatient settings across the Veterans Health Administration (VHA) over 18 years. Methods: We analyzed a retrospective cohort of all patients who had any positive clinical culture specimen for ESCR Enterobacteriaceae collected in an outpatient setting; ESCR was defined by phenotypic nonsusceptibility to at least one extended-spectrum cephalosporin agent or detection of an extended-spectrum β-lactamase. Patient-level data were grouped by county of residence, and the total number of unique patients who received care within VHA for each county was used as a denominator. We aggregated data by time terciles (2000–2005, 2006–2011, and 2012–2017), and overall and county-level incidence rates were calculated as the number of unique patients in each year with ESCR Enterobacteriaceae per person-year. Results: During the study period, there were 1, 980, 095 positive cultures for Enterobacteriaceae from 870, 797 unique patients across outpatient settings of VHA, from a total of 107, 404, 504 person-years. Among those, 136, 185 cultures (6.9%) from 75, 500 unique patients (8.7%) were ESCR. The overall incidence rate was 9.0 cases per 10, 000 person-years, which increased from 6.3 per 10, 000 person-years in 2000 to 14.6 per 10, 000 person-years in 2017. County-level incidence rates ranged widely but increased overall (interquartile range [IQR] in 2000–2005: 0–6.7; 2006–2011: 0–9.1; 2012–2017: 3.1–14.3 per 10, 000 person-years), with some geographic clustering (figure). Conclusion: This study demonstrates that there has been geographic variation both in incidence rates and trends of ESCR Enterobacteriaceae in outpatient settings of VHA, which suggests the importance of tailoring local antibiotic-prescribing guidelines incorporating geographic variability in epidemiology. Disclosures: M. Ohl, Gilead Sciences, Inc.: Grant Investigator, Research grant.